Green Trend in Global Energy Development: Tendencies and Opportunities - Petrenko, Larisa D. (International Journal of Energy Economics and Policy, 2021)
The actualization of global environmental problems necessitates transformational changes in the global energy sector. The intensification of global trends toward decarbonization leads to alteration in the energy sector. The sustainable development of the renewable energy sector is driven by the greening of global development and will be long-term in nature due to a progressive reduction in its cost and the achievement of stable energy efficiency indicators. The intensive growth of the renewable energy sector is primarily supported by government financial support as part of sustainable development strategies. Various forms of state support for projects for the development of alternative energy sources are used in achieving targets for the potential of renewable energy sources at the national level. Its role gradually decreases as the degree of maturity of alternative energy is reached. Further development of energy policies at the national level will take place in the increased use of market support instruments. Keywords: Global Energy; Sustainable Development; Renewable Energy Sources; Green Economy; Decarbonization; Energy Policy JEL Classifications: O13; P28; Q42; Q56 DOI: https://doi.org/10.32479/ijeep.11094